Involvement of Wnt, Eda and Shh at defined stages of sweat gland development - Cui, Chang-Yi; Yin, Mingzhu; Sima, Jian; Childress, Victoria; Michel, Marc; Piao, Yulan; Schlessinger, David (Development (Cambridge), 2014)
To maintain body temperature, sweat glands develop from embryonic ectoderm by a poorly defined mechanism. We demonstrate a temporal cascade of regulation during mouse sweat gland formation. Sweat gland induction failed completely when canonical Wnt signaling was blocked in skin epithelium, and was accompanied by sharp downregulation of downstream Wnt, Eda and Shh pathway genes. The Wnt antagonist Dkk4 appeared to inhibit this induction: Dkk4 was sharply downregulated in β-catenin-ablated mice, indicating that it is induced by Wnt/β-catenin; however, its overexpression repressed Wnt target genes and significantly reduced gland numbers. Eda signaling succeeded Wnt. Wnt signaling was still active and nascent sweat gland pre-germs were still seen in Eda-null mice, but the pre-germs failed to develop further and the downstream Shh pathway was not activated. When Wnt and Eda were intact but Shh was ablated, germ induction and subsequent duct formation occurred normally, but the final stage of secretory coil formation failed. Thus, sweat gland development shows a relay of regulatory steps initiated by Wnt/β-catenin - itself modulated by Dkk4 - with subsequent participation of Eda and Shh pathways.